Ternary Pd–Ni–P hybrid electrocatalysts derived from Pd–Ni core–shell nanoparticles with enhanced formic acid oxidation activity. Issue 74 (23rd August 2016) - Liang, Xin; Liu, Bo; Zhang, Juntao; Lu, Siqi; Zhuang, Zhongbin
Abstract : Highly active formic acid electro-oxidation performance was achieved by using ternary Pd–Ni–P hybrid electro-catalysts with a strong synergistic effect. Abstract : Ternary Pd–Ni–P hybrid electrocatalysts were synthesized through low temperature phosphidation of Pd–Ni core–shell nanoparticles. They show enhanced formic acid electro-oxidation activity compared to Pd, Pd–Ni and Pd–P nanoparticles, which is ascribed to the synergistic effect of the Ni and P components with Pd.